Discovery of 5-methylpyrimidopyridone analogues as selective antimycobacterial agents. (1st November 2021) - Wu, Yu; Cheung, Chen-Yi; Zhou, Yang; Wang, Zhen; Tu, Zhengchao; Cook, Gregory M.; Lu, Xiaoyun
Graphical abstract: A series of 5-methylpyrimidopyridone analogues were designed and synthesized as potential antitubercular agents. Compound 6q exhibited the most potent activity with MIC value of 4 μM. Abstract: With the emergence of multidrug-resistant strains of Mycobacterium tuberculosis (MDR-TB) and extensive drug-resistant strains (XDR-TB), there is an urgent need to develop novel drugs for the treatment of tuberculosis. Here, we designed and synthesized a series of 5-methylpyrimidopyridone analogues as potential antitubercular agents. The most potent compound 6q exhibited a MIC value of 4 μM in vitro against Mycobacterium tuberculosis . The antitubercular activities of the synthesized compounds were impacted by the amantadine and 2-chlorophenyl groups, and were enhanced by the presence of 3-methyl(4-dimethylamino)piperidinylphenyl. Molecular modeling and binding studies suggest that PknB is the potential molecular target of 5-methylpyrimidopyridone compounds. This study provides insights for the future development of new antimycobacterial agents with novel mechanisms of action.